IJCM_35A: Prevalence and risk factors for domestic violence against infertile women in central India - Katole Ashwini; Saoji Ajeet; Ruikar Manisha (Wolters Kluwer Medknow Publications, 2024)
Background: Infertility is a public health issue affecting a large part of the world's population. Violence against women, Spousal or intimate partner violence is the most common form of domestic violence; a preventable cause of morbidity and mortality in women. Especially sexual violence, is one of the most pressing public health concerns affecting women today. Objective: To estimate the prevalence of spousal violence, various types of spousal violence and factors associated with it among reproductive age group women. Methodology: This was an analytical cross-sectional study conducted in Urban Health Training Centre area of a tertiary care teaching hospital in Nagpur, India among married women between 15-49 years of age. The reproductive age group women were 3985 according to health survey done by UHTC. Out of which the data was collected in a sample of 82 infertile women by face-to-face interview and analysed using SPSS v22. Predesign pretested questioner use for data collection. The ethical consideration was taken from the institute for the study. Results: The prevalence of spousal violence among reproductive age group (15-49 years) women was found to be 79.7%; emotional violence (64.1%) being the most common, followed by physical (71.2%) and sexual (53.6%) violence in that order Conclusion: Infertility and associated domestic violence is a significant public health issue, it would be necessary to pay attention to infertile women to ensure the quality of their of reproductive health.